2017
DOI: 10.1177/0972063417699691
|View full text |Cite
|
Sign up to set email alerts
|

Why Members Dropout? An Evaluation of Factors Affecting Renewal in Micro Health Insurance

Abstract: Micro health insurance (MHI) is an important mechanism to fight iatrogenic poverty in India. Its sustainability and viability depends, to a greater extent on the renewal of membership. This article evaluates the factors that influence renewal decisions in Sampoorna Suraksha Programme (SSP) in Karnataka. This study shows income class and chronic illness in the family to determine the renewability. The findings indicate adverse selection since low-income low-risk and high-income low-risk families dropout. From t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(27 citation statements)
references
References 4 publications
3
24
0
Order By: Relevance
“…29,36 Level of education also plays an important role in influencing the members' renewal decision as 12 of the 14 studies showed a positive association between higher levels of education and renewal decision [26][27][28][29][30][31][32][33]36,40,41,43 among 364 which seven studies revealed a statistically significant correlation. 26,27,29,31,33,36,41 Contrary to this, those who attain higher education were less likely to renew membership as noted by two studies, 25,34 but it is not statistically significant in both reports. The level of education was also used inconsistently in the included studies.…”
Section: Theme 1: Socio-demographic Factorsmentioning
confidence: 71%
See 3 more Smart Citations
“…29,36 Level of education also plays an important role in influencing the members' renewal decision as 12 of the 14 studies showed a positive association between higher levels of education and renewal decision [26][27][28][29][30][31][32][33]36,40,41,43 among 364 which seven studies revealed a statistically significant correlation. 26,27,29,31,33,36,41 Contrary to this, those who attain higher education were less likely to renew membership as noted by two studies, 25,34 but it is not statistically significant in both reports. The level of education was also used inconsistently in the included studies.…”
Section: Theme 1: Socio-demographic Factorsmentioning
confidence: 71%
“…The review included 27 papers: 19 quantitative, [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39][40][41][42] two mixed-method, 43,44 and six qualitative types of research. [45][46][47][48][49][50] The studies were conducted in 12 countries (seven LMICs) across two continents (Asia and Africa) among which the largest number of papers was conducted in Sub-Saharan Africa countries.…”
Section: Characteristics Of Included Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…5,6 A continuous increase in dropout would be a death knell for the viability of any scheme because decreasing the risk pool would squeeze resource mobilization and end up with financial losses. 7 The difficulty of enrolling and retaining membership for the less endowed is seen as a reason why schemes in low-income and middle-income countries (LMICs) often fail to secure satisfactorily enrolment levels. 8 Individuals at low risk of falling ill dropout of the scheme, leaving only the high-risk individuals, which leads to the collapse of the CBHI schemes and compromises its sustainability.…”
Section: Introductionmentioning
confidence: 99%